Analisis Persediaan Bahan Baku Penolong Menggunakan Metode ABC pada PGT Rejowinangun Trenggalek - Limbong, Albert Christian; Wulandari, Lusi Mei Cahya (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The research at PGT Rejowinangun Trenggalek aims to enhance efficiency and effectiveness using the ABC method formula. The research results reveal three categories of raw material components. Category A involves 2 items with a total cost of IDR 133,810,000, contributing approximately 79 percent of the total inventory funds. Category B includes 1 item, constituting around 7 percent of the total items, with an absorption cost of IDR 12,600,000. Category C comprises 3 items, accounting for about 13 percent of the total items. The ABC analysis provides an overview of cost distribution and raw material turnover, serving as a basis for efficient order planning.